Vertical Sterilizer Design of Building Palm Oil Processing Plant to Cost Efficiency. (October 2019) - Rizkya, I; Syahputri, K; Erwin,
Abstract: Research is carried out in the Palm Oil Processing Plant is being built. The establishment of a factory experienced cost problem due to the increasing price of products import. This study describes the application of value engineering to find the highest cost components and alternative designs are able to replace the initial design and the building cost in the factory can be reduced. Vertical sterilizer is known to be the largest cost component followed by the cost of the Valves and Hydraulic System Control Unit. The company is currently designing to replace 4 units vertical sterilizer capacity 10 tons fresh fruit bunches with 3 units vertical sterilizer capacity 15 tons fresh fruit bunches. The change in the quantity and capacity of the vertical sterilizer is followed by a reduction quantity of Control Units c / w Valves and Hydraulic Systems used. As a result of this design change, the initial life cycle cost is IDR 7.531.154.360, - decrease to IDR 6.642.162.754, -. By using value engineering, it is able to make the cost efficiency in a factory about 11, 8%.